Pemberdayaan UMKM Binaan IPEMI Kota Palangka Raya melalui Pemasaran Digital dan Implementasi Islamic Sociopreneurship: Empowering MSMEs Fostered by IPEMI in Palangka Raya City Through Digital Marketing and Implementation of Islamic Sociopreneurship - Rozikin, Achmad Zainul; Annisa, Nur; Miftahurrizqi, Miftahurrizqi; Charita, Bintang Aurellia; Hidayah, Nurul (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
MSMEs fostered by IPEMI Palangka Raya City face two main challenges: marketing and management. Marketing is evidenced by limited market reach, characterized by a lack of social media promotion. Management is also affected by the lack of technology utilization in entrepreneurship. This can lead to inefficient work. This community service activity aims to improve the capacity and competence of MSMEs fostered by IPEMI Palangka Raya City through training and mentoring in digital marketing and the implementation of Islamic sociopreneurship. In digital marketing, the Community Service Program (PKM) team trained and guided MSMEs in the use of several applications, such as Canva and Capcut. Furthermore, the PKM team also advised MSMEs to maximize the use of social media (WhatsApp, Instagram, and TikTok) and utilize online stores (e-commerce) such as Tokopedia and Shopee to reach a wider market. In management, MSMEs received training on the application of the Islamic sociopreneurship business model and the use of the Qasir application for financial management. The results of this community service demonstrate an increase in the understanding and competency of MSMEs in visual marketing and creative content, e-commerce marketing, the development of Islamic socio-entrepreneurship business models, and financial and operational management. In conclusion, this community service activity can encourage MSMEs to compete in the era of globalization and maintain sustainable businesses.